Phenoxytacrine derivatives: Low-toxicity neuroprotectants exerting affinity to ifenprodil-binding site and cholinesterase inhibition - Misiachna, Anna; Svobodova, Barbora; Netolicky, Jakub; Chvojkova, Marketa; Kleteckova, Lenka; Prchal, Lukas; Novak, Martin; Hrabinova, Martina; Kucera, Tomas; Muckova, Lubica; Moravcova, Zuzana; Karasova, Jana Zdarova; et al. (European journal of medicinal chemistry, 2024)
Tacrine (THA), a long withdrawn drug, is still a popular scaffold used in medicinal chemistry, mainly for its good reactivity and multi-targeted effect. However, THA-associated hepatotoxicity is still an issue and must be considered in drug discovery based on the THA scaffold. Following our previously identified hit compound 7-phenoxytacrine (7-PhO-THA), we systematically explored the chemical space with 30 novel derivatives, with a focus on low hepatotoxicity, anticholinesterase action, and antagonism at the GluN1/GluN2B subtype of the NMDA receptor. Applying the down-selection process based on in vitro and in vivo pharmacokinetic data, two candidates, I-52 and II-52, selective GluN1/GluN2B inhibitors thanks to the interaction with the ifenprodil-binding site, have entered in vivo pharmacodynamic studies. Finally, compound I-52, showing only minor affinity to AChE, was identified as a lead candidate with favorable behavioral and neuroprotective effects using open-field and prepulse inhibition tests, along with scopolamine-based behavioral and NMDA-induced hippocampal lesion models. Our data show that compound I-52 exhibits low toxicity often associated with NMDA receptor ligands, and low hepatotoxicity, often related to THA-based compounds.
Keywords: Alzheimer's disease; receptory N-methyl-D-aspartátu; Electrophysiology; Acetylcholinesterase; neuroprotektivní látky; cholinesterasové inhibitory; acetylcholinesterasa; Neuroprotective Agents; takrin; Tacrine; Cholinesterase Inhibitors; Receptors, N-Methyl-D-Aspartate; Alzheimer Disease; Glutamate receptor; In vivo; Neuroprotection; Piperidines; Cholinesterases; Humans; Binding Sites; cholinesterasy; Alzheimerova nemoc; lékové postižení jater; piperidiny; vazebná místa; lidé; Chemical and Drug Induced Liver Injury